Peningkatan Literasi Keuangan Untuk Peningkatan Kinerja Dan Keberlangsungan UMKM Kota Jambi - Adria Wuri Lastari; Indah Mutiara; Efandri Agustian; Sri Mulyani (Universitas Batanghari, 2023)
Micro, Small and Medium Enterprises (UMKM) experience various kinds of problems. One of the problems faced by UMKM is related to capital and business sustainability due to changing environmental conditions which have an impact on decreasing income levels. This research aims to examine the influence of financial literacy on business performance and sustainability of UMKM in Jambi. The research was conducted using a quantitative approach by giving questionnaires to respondents. The sampling technique uses purposive sampling by considering UMKM respondents in Jambi who have been established for more than one year and are still actively running their businesses. The analytical method in this research The sampling technique used was accidental sampling of 55 respondents from food and beverage UMKM owners in Jambi. The data analysis technique uses simple linear regression analysis. Based on the results of the t test (partial), it states that Financial Literacy has an influence on MSME Performance, where the t-count > t-table value, namely 3.307 > 1.674, which means that Financial Literacy has a significant influence on UMKM Performance. Meanwhile, for the test of the Financial Literacy variable on the Sustainability of MSMEs, it also has an influence, where the Financial Literacy variable has a t-count > t-table value, namely 3.906 > 1.674, which means that Financial Literacy has a significant influence on the Sustainability of UMKM.